Effectiveness of integrated chronic care interventions for older people with different frailty levels: a systematic review protocol - Gurch Randhawa; David Hewson; Nimra Khan (BMJ Open)
Introduction Frailty poses a huge burden to individuals, their families and to healthcare systems. Several interventions have been evaluated for the improvement of outcomes for older people with frailty, including integrated care interventions. Reviews synthesising evidence on the effectiveness of integrated care for older people with frailty have treated them as a single population, without considering the heterogeneity between different frailty levels such as non-frail, mild frailty, moderate frailty and severe frailty. Findings from these studies have shown inconsistent results on the various outcomes assessed. People with different frailty status have different care needs, which should be addressed accordingly. The aim of this study is to synthesise evidence on the effectiveness of integrated care interventions on older people with different frailty status who are community dwelling or living in retirement housing or residential setting but not in care homes or in nursing homes.Methods and analysis This is a protocol for a systematic review assessing the effectiveness of integrated chronic care interventions on older people with different frailty status. A literature search will be conducted on the databases Cochrane Central Register of Controlled Trials, PubMed, Embase, Web of Science, Cumulative Index to Nursing and Allied Health Literature, and clinical trial registers. Two authors will independently conduct search and screening for eligible studies. Full-text screening will be used to include only studies that fulfil the inclusion criteria. Data extraction will be done on a data extraction form and methodological quality of studies will be assessed using the Effective Practice and Organisation of Care risk of bias tool. The interventions will be described following Wagner’s Chronic Care Model.Ethics and dissemination Ethical approval for this study was obtained from the Institute for Health Research Ethics Committee of the University of Bedfordshire (IHREC934). The results of the review will be disseminated through a peer-reviewed journal article, conferences and also with local provider and user stakeholders.PROSPERO registration number CRD42020166908.